Labouring men : studies in the history of labour - Hobsbawm, Eric John (London : Weidenfeld and Nicolson, 1979)
Bibliotheek François Vercammen
Engels
Monografie
Keywords: 19e eeuw; arbeidsomstandigheden; levensomstandigheden; Groot-Brittannië.